2012
DOI: 10.3892/ol.2012.1042
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensitizing activities of cyclotides from Clitoria ternatea in paclitaxel-resistant lung cancer cells

Abstract: Cyclotides comprise a family of circular mini-peptides that have been isolated from various plants and have a wide range of bioactivities. Previous studies have demonstrated that cyclotides have antitumor effects and cause cell death by membrane permeabilization. The present study aimed to evaluate the cytotoxicity and chemosensitizing activities of cyclotides from Clitoria ternatea in paclitaxel-resistant lung cancer cells. In this study, a total of seven cyclotides were selected for colorimetric cell viabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 21 publications
0
35
0
1
Order By: Relevance
“…A study carried out by Sen et al (2013) has isolated five cyclotides named CT2, CT4, CT7, CT10, and CT12 (with an addition or removal of a net charge from −1 to +2) from this plant species. They showed significant cytotoxicity against human lung cancer cells (A549) and demonstrated a reduction of 2- to 4-fold of the IC 50 (half maximal inhibitory concentration) value of cyclotides when compared to a mitotic inhibitor used in cancer chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study carried out by Sen et al (2013) has isolated five cyclotides named CT2, CT4, CT7, CT10, and CT12 (with an addition or removal of a net charge from −1 to +2) from this plant species. They showed significant cytotoxicity against human lung cancer cells (A549) and demonstrated a reduction of 2- to 4-fold of the IC 50 (half maximal inhibitory concentration) value of cyclotides when compared to a mitotic inhibitor used in cancer chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…They showed significant cytotoxicity against human lung cancer cells (A549) and demonstrated a reduction of 2- to 4-fold of the IC 50 (half maximal inhibitory concentration) value of cyclotides when compared to a mitotic inhibitor used in cancer chemotherapy. Moreover, these peptides were less cytotoxic against A549/paclitaxel (a sub-linage of A594) than only A549, which demonstrates a possible use of chemo-sensitization for treating cancer (Sen et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…More recently, cliotide CT2 was found to have activity against human nonsmall lung cancer cells (A549; IC 50 = 7.6 μM) and an A549-derived paclitaxel-resistant sub-line (A549/taxol; IC 50 = 7.9 μM). However, in the case of A549/taxol cells this IC 50 was reduced to 1.62 μM when these cells were exposed to 50:50 ratios of cliotide CT2 and paclitaxel [68], which is another well-established anticancer drug [69]. These observations indicated a synergistic action between paclitaxel and cliotide CT2 and showed that the peptide was able to chemosensitize cancer cells to conventional anticancer drugs [68].…”
Section: Ahdps From Cyclotidesmentioning
confidence: 83%
“…For example, PE shows the potential to serve as a biomarker for many malignancies [98] and it has been proposed that derivatives of PE-binding cyclotides may be suitable for development as agents in tumour imaging and anticancer therapeutics [75,76,81,99,100]. As another example, it may be possible to optimise the membrane-permeabilizing ability of cyclotides through scaffold modification to efficiently synergise the action of established anticancer drugs, as described above for cliotide CT2 and paclitaxel [68]. Proof-of-concept for such work was recently demonstrated when a grafted cyclotide, showed activity against growth factors involved in angiogenesis [101]; it is well-established that tumor growth is usually associated with unregulated angiogenesis [102].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation